Maps as Knowledge Aggregators: from Renaissance Italy Fra Mauro to Web Search Engines - Nanetti, Andrea (2016)
Mediaeval and Renaissance maps of the world were and worked as knowledge aggregators. The cosmographers identified, selected and re-edited information about hundreds of places from a variety of literary, iconographic and oral sources, and synoptically re-organized them in place names, cartouches, and drawings to be put on a map. This selection/aggregation process transformed the mappa mundi into a visual encyclopaedia (i.e. an all-around learning and thinking tool), where each geographical entry was able to generate narratives as a data gateway and an information hub for customs, commodities, and rulers of different peoples of the world. If we infer that the Renaissance people asked to the cosmographers to learn about the world as we go to search engines to find what we want, the reverse engineering of these works (as exemplified in this paper for the mid-fifteenth-century world map by Fra Mauro Camaldolese) can help to draw the connection between the traditional way to aggregate knowledge as a product (e.g. Fra Mauro’s mappa mundi) and the modern way of using search engines and related internet services (i.e. their map services) to serve a similar purpose but in a better and more dynamic manner, placing crucial question, such as: How the same networks/people can bring new wealth and development, or war and poverty? Which are the dynamics of sustainability in international mechanisms?